Health care utilization for pain in children and adolescents: a prospective study of laboratory and non-laboratory predictors of care-seeking - Tsao, Jennie C. I. (2011)
BACKGROUND: Few studies have focused on identifying predictors of medical consultation for pain in healthy children and adolescents. OBJECTIVE: This investigation sought to identify parent and child laboratory and non-laboratory predictors of pediatric healthcare utilization for pain problems. STUDY GROUP: Participants were 210 healthy children and adolescents (102 girls), aged 8–17 years who took part in a laboratory pain session. METHODS: Three months after the laboratory session, participants were contacted by telephone to ascertain whether they had experienced pain and whether they had seen a healthcare professional for pain. Zero-order correlations among sociodemographics, child laboratory pain responses, parent physical/mental health status and medical consultation for pain were conducted to identify relevant correlates of pediatric healthcare utilization; these correlates were subjected to multivariate analyses. RESULTS: Bivariate analyses indicated that higher anticipated pain and bother for the cold pressor task, as well as poorer parent physical health status, were associated with pediatric medical consultation for pain, but only among girls. Sequential logistic regression analyses controlling for child age indicated that only parent physical health status, not the laboratory indicators, significantly predicted healthcare consultation for pain among girls. No parent or child correlates of care-seeking for pain emerged for boys. CONCLUSION: The findings suggest that parents’ perceived physical health plays a role in determining whether medical care is sought for pain complaints in healthy girls. These results suggest that interventions to assist parents in managing their own physical health problems may lead to reductions in medical consultation for girls’ pain.